Talent management : a research overview - McDonnell, Anthony; Wiblen, Sharna L. (Oxon: Routledge, 2021)
"Talent management is a central element of managerial discourse and organisational practice. This shortform book provides a succinct overview on the state of research on talent management. The authors set out the key themes, arguments, trends, and future research trajectories of talent management, highlighting major works in the field. As a research topic with a fragmented body of knowledge, pluralistic perspectives are summarised, whilst workforce differentiation emerges as a central element. A critical introduction for students, scholars and reflective practitioners, this shortform book guides readers through a relatively new and rapidly developing area of management research. Anthony McDonnell is Full Professor of Human Resource Management and Head of the Department of Management and Marketing at the Cork University Business School, University College Cork, Ireland. He has held appointments at Queen's University Belfast, University of South Australia and University of Newcastle, Australia. His research has been funded by the Australian and Irish Research Councils and Ireland Canada University Foundation. Sharna Wiblen is Assistant Professor at the Sydney Business School, University of Wollongong, Australia. Sharna blends academic skills and 15 years of industry experience including time as a management consultant, human resource and recruitment coordinator, and retail service manager to broker dialogue between academics and industry to advance the study and practice of responsible talent management"--
Includes bibliographical references and index.
Keywords: Personnel management; Ability; Employee motivation; Success